Knowledge gaps in patients with atrial fibrillation revealed by a new validated knowledge questionnaire. (15th November 2016) - Desteghe, Lien; Engelhard, Lara; Raymaekers, Zina; Kluts, Kiki; Vijgen, Johan; Dilling-Boer, Dagmara; Koopman, Pieter; Schurmans, Joris; Dendale, Paul; Heidbuchel, Hein
Abstract: Objective: The aim of this study was to develop and validate a new questionnaire, the Jessa Atrial fibrillation Knowledge Questionnaire (JAKQ), to test the knowledge of patients with atrial fibrillation (AF) about the arrhythmia, its treatment and their ability for self-management. Methods: The JAKQ was developed based on other questionnaires, two educational checklists and patient information support websites. The JAKQ was validated based on content validity, face validity, response process, discriminatory potential and sensitivity of the questionnaire, construct validity and reliability. It was presented to both outpatients and hospitalised patients. Results: A total of 466 AF patients completed the JAKQ. The final 16-item JAKQ consists of 8 questions about AF in general, 5 questions about oral anticoagulation (OAC) therapy and either 3 questions about vitamin K antagonists (VKA) or non-vitamin K antagonist oral anticoagulants (NOAC). The questionnaire is completed in 6.5 ± 2.4 min. The mean score on the JAKQ is 55.8 ± 18.6% with a wide discriminatory span of scores. The JAKQ reveals important knowledge gaps, like 28.8% of the patients not being aware of their medical condition named 'atrial fibrillation', 33.7% being unaware that AF can cause thromboembolism and stroke, and 78.6% of the patients taking VKA and 57.0% of the patients on NOACs not knowing what to do when missing an OAC dose. Conclusions: The JAKQ is a brief, complete and valid AF-specific knowledge questionnaire that can be used in daily practice to assess patients' insight into their condition. It could be used as a tool for individually tailored patient education.